2020
DOI: 10.1002/mabi.202000085
|View full text |Cite
|
Sign up to set email alerts
|

Design of Hydrolytically Degradable Polyethylene Glycol Crosslinkers for Facile Control of Hydrogel Degradation

Abstract: matrix-type devices, without requiring surgical removal. [7-9] Enzymatic and hydrolytic degradation are the two major physiologically relevant mechanisms that confer degradability to hydrogel matrices. Enzymatic degradation is generally preferred in tissue engineering, where matrix degradation must be synchronized with native cell infiltration and tissue deposition. [10,11] Enzymatically degradable gels have also shown great potential for celldemanded growth factor delivery, where growth factors are released u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Due to its dual ionic nature, SPP is commonly used to de-gel self-gelling grades of laponite when added at a concentration of 1–10% by mass of NS. , In particular, pyrophosphate anions in SPP shield the NS particle edges, leading to the entire particle having a negative charge. , Then, sodium cations in SPP loosely associate around the particles, causing mutual repulsion between them. PBS is a common physiological buffer, and TEA is a mild base needed for PEG hydrogel formation. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its dual ionic nature, SPP is commonly used to de-gel self-gelling grades of laponite when added at a concentration of 1–10% by mass of NS. , In particular, pyrophosphate anions in SPP shield the NS particle edges, leading to the entire particle having a negative charge. , Then, sodium cations in SPP loosely associate around the particles, causing mutual repulsion between them. PBS is a common physiological buffer, and TEA is a mild base needed for PEG hydrogel formation. , …”
Section: Resultsmentioning
confidence: 99%
“…PBS is a common physiological buffer, and TEA is a mild base needed for PEG hydrogel formation. 4,34 The buffer in which NS was dispersed had a significant effect on NS dispersion (Figure 1). PBS and TEA were ineffective at dispersing NS particles, with large aggregates remaining even after sonication.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Alternatively, hydrolytic degradation of PEG-based hydrogels may be engineered by synthesizing ester-containing cross-linkers with different hydrolytic susceptibility, such as groups with steric hindrance, local hydrophobicity, and electron-withdrawing moieties. 3,7 Among the various cross-linking chemistries, PEG-based hydrogels fabricated by orthogonal thiol-norbornene photopolymerization are increasingly used in drug delivery and tissue engineering applications. 8 In particular, multiarm PEGnorbornene (PEGNB) can be cross-linked into an idealized network using a multifunctional thiol cross-linker through a radical-medicated thiol-norbornene reaction initiated by ultraviolet light, 9−12 visible light, 13,14 or enzymatic reaction.…”
mentioning
confidence: 99%
“…On the other hand, labile motifs (e.g., poly­(lactic acid), PLA) are routinely copolymerized with functionalized PEG to render the otherwise stable network hydrolytically labile. Alternatively, hydrolytic degradation of PEG-based hydrogels may be engineered by synthesizing ester-containing cross-linkers with different hydrolytic susceptibility, such as groups with steric hindrance, local hydrophobicity, and electron-withdrawing moieties. , …”
mentioning
confidence: 99%
“…The authors demonstrated that degradation could be decoupled from the initial mechanical properties. Kroger et al 434 showed that for hydrogels crosslinked via thiol−acrylate Michael-type reaction, the degradation rate could be controlled by modifying the chemistry adjacent to the carbonyl carbon in the cross-link without substantially changing the initial mechanical properties. The authors showed that these modifications led to degradation times that ranged from hours to weeks.…”
Section: Growth and Development Of Neo-tissue In Degrading Hydrogelsmentioning
confidence: 99%